Turkey and the European Community - Zentrum für Türkeistudien. author. aut Link
119 p. 8 illus.
Keywords: Nearly 29 years have passed since the EC and Thrkey forged the Association Agreement on 12.3.63. After abrief period on hold, Thrkish-EC relations regained dynamism when Thrkey applied for full membership on April 14, 1987. The view of the EC Commission, as presented some two and a half years later to the Council of Ministers, was approved by EC Foreign Ministers. The response stated that the EC would not start negotiations for membership until the completion of the Single Market. The main points of the Commission's observation focused on the discrepancy in the levels of economic development between Turkey and the EC, the issue of human rights, shortcomings in social security and the question of Cyprus. This response was a source of great disappoinment in Thrkey; because it had been a consistent ally of the West until then, taken important steps towards democracy and a free-market economy, EC membership, as Thrkey saw it, was to be its reward.